Moringa Leaf Extract Capsules Enriched with Royal Jelly on Cortisol and Stress - Dwi Kartika Sari; Veni Hadju; Werna Nontji; Mardiana Ahmad; Aryadi Arsyad; Andi Nilawati Usman; Yudi Yanto; Taqwin Taqwin (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
During pregnancy, physiological and psychological changes often increase stress and cortisol levels. Administering moringa leaf extract capsules fortified with royal jelly presents a viable intervention to alleviate this stress. This study investigates the specific effects of these capsules on cortisol and stress levels in pregnant women. The study was conducted as a true experimental, single-blind, randomized controlled trial involving 61 pregnant women. The intervention group (n = 31) received moringa leaf extract capsules enriched with royal jelly, while the control group (n = 30) received multi-micronutrient supplements. The findings revealed a noteworthy reduction in cortisol levels within the intervention group (p = 0.030), from 26.61 ± 8.15 to 19.98 ± 14.00, as well as in the control group (p = 0.003), from 21.13 ± 7.76 to 13.26 ± 16.09. Likewise, stress levels exhibited a significant decrease within the intervention group (p = 0.016), decreasing from 18.68 ± 3.74 to 28.75 ± 15.02, and the control group (p = 0.000), declining from 19.17 ± 3.64 to 16.20 ± 3.38. Moringa leaf extract capsules enriched with royal jelly, as a natural remedy, merit the recommendation for inclusion in initiatives to enhance maternal and infant health.